2018
DOI: 10.1016/j.heliyon.2018.e00527
|View full text |Cite
|
Sign up to set email alerts
|

Currently available murine Leydig cell lines can be applied to study early steps of steroidogenesis but not testosterone synthesis

Abstract: Androgen biosynthesis in males occurs to a large extent in testicular Leydig cells. This study focused on the evaluation of three murine Leydig cell lines as potential screening tool to test xenobiotics interfering with gonadal androgen synthesis. The final step of testosterone (T) production in Leydig cells is catalyzed by the enzyme 17β-hydroxysteroid dehydrogenase 3 (17β-hsd3). The endogenous 17β-hsd3 mRNA expression and Δ4-androstene-3,17-dione (AD) to T conversion were determined in the murine cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In TM3 cells, Star gene expression was significantly increased by Start overexpression (Figure 10B), and in MA-10 cells, not only Star but also Cyp17a1, Hsd3b1, and Hsd17b3 genes were significantly upregulated by Start (Figure 10D). We failed to detect testosterone in the culture media of MA-10 cells overexpressing Start, probably due to low capability of testosterone production of this cell line as previously reported (67,68). These results supported the notion that Start acts as an activator of steroidogenic genes in Leydig cells, as shown by results for 8-day-old mice (Figure 9A).…”
Section: Activation Of Steroidogenic Genes By Start In Leydig Cell Linessupporting
confidence: 90%
“…In TM3 cells, Star gene expression was significantly increased by Start overexpression (Figure 10B), and in MA-10 cells, not only Star but also Cyp17a1, Hsd3b1, and Hsd17b3 genes were significantly upregulated by Start (Figure 10D). We failed to detect testosterone in the culture media of MA-10 cells overexpressing Start, probably due to low capability of testosterone production of this cell line as previously reported (67,68). These results supported the notion that Start acts as an activator of steroidogenic genes in Leydig cells, as shown by results for 8-day-old mice (Figure 9A).…”
Section: Activation Of Steroidogenic Genes By Start In Leydig Cell Linessupporting
confidence: 90%
“…Several studies had previously established that TM3 cells are suitable for use in the determination of testosterone production (Ilfergane & Henkel, 2018; Jambor et al., 2019; Lin et al., 2019; Liu et al., 2016; Xia et al., 2020). However, another study demonstrated that unstimulated and stimulated TM3 cells produced a low amount of testosterone and a high amount of progesterone, suggesting that TM3 cells are unsuitable for studying the gonadal androgen biosynthesis due to altered steroidogenic pathways (Engeli, Fürstenberger, Kratschmar, & Odermatt, 2018). However, the effect of MO on progesterone levels in the TM3 cells was not included in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to primary Leydig cells, MA-10 cells proliferate and contain an aberrant chromosome number [ 32 ]. Despite these issues, MA-10 cells nonetheless respond to hormonal stimulation, like primary Leydig cells, with an increase in steroid hormone production [ 30 , 33 , 34 , 35 , 36 ], indicating that the signalling cascades, kinases, and transcription factors required for this response are present in MA-10 Leydig cells. More relevant to our current work, MA-10 Leydig cells constitutively express Insl3 [ 13 , 19 , 22 , 23 , 27 , 37 , 38 , 39 ] and have been validated as a suitable model to study Insl3 gene transcription [ 27 ].…”
Section: Discussionmentioning
confidence: 99%